The peptide regulator Vezusten in the management of overactive bladder syndrome: an efficacy evaluation - G. V. Kovalev; I. A. Labetov; R. R. Shakirova; D. D. Shkarupa (Вестник урологии, 2024)
Introduction. Overactive bladder (OAB) remains one of the most difficult-to-treat conditions in neurourology. The number of patients seeking help for OAB symptoms does not decrease each year, while a pathogenetic treatment has not yet been developed. This motivates the search for new approaches.Objective. To assess the efficacy of the peptide regulator Vezusten for women with idiopathic OAB based on their health condition and urodynamic assessment of bacterial detrusor overactivity (DO).Materials & methods. A prospective cohort study included 20 patients diagnosed with OAB, which was confirmed by a comprehensive urodynamic study of DO. The patients visited the clinic three times a week. Each patient received ten intramuscular injections of the peptide regulator Vezusten. Within one month after the last injection, the women were given a monitoring voiding diary, a validated Continental Society OAB Symptom Questionnaire, the Overactive Bladder Questionnaire (OAB-q), and a follow-up urodynamic study (UDS).Results. We obtained statistically significant differences in the following indicators: the number of daily urinations according to the urination diary decreased from 14.0 [13.0; 16.3] to 11.0 [8.8; 12.0] (p < 0,001), patient’s episodes of urge incontinence began to be noted for the first time (p = 0.004). At the same time, the urodynamic maximum cystometric capacity (MCC) increased from 267 [158; 332] to 320 [267; 433] ml. Subjectively, participants noted an improvement in the scores of the OAB questionnaire (OAB-q) — the score decreased from 28 [22; 30] to 19 [14; 24] (p = 0.001), and the number of episodes of nocturia decreased from 4 to 2 (p < 0.001). No side effects from therapy were observed in any of the patients.Conclusion. This study demonstrated a statistically significant improvement in subjective symptoms of OAB in DO-women treated with the peptide regulator Vezusten, but further large placebo-controlled studies are required for confirmation.